Science for Agriculture and Rural Development in Low-income Countries - Roetter, Reimund P.; Keulen, Herman Van.; Kuiper, Marijke; Verhagen, Jan.; Laar, H. H. Van.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Since 1998, the Dutch Ministry of Agriculture, Nature Management and Food Quality (LNV) promotes development-orientated agricultural and environmental research and strengthening of North-South partnerships through its International Cooperation (DLO-IC) research programme. By 2005, some 70 collaborative North-South projects had been carried out. All science groups in Wageningen University and Research Centre (WUR) were involved in the implementation of the programme and at least half the projects and activities undertaken were directly related to Rural Development and Sustainable Agriculture (RDSA). Facing new challenges with respect to sustainable development strategies for low-income countries, related to global environmental change and globalization of markets, an interdisciplinary Wageningen research group set out to draw lessons from the DLO-IC projects of the last eight years, stimulate discussion and support identification of a future research agenda for RDSA. In that process, special emphasis was given to lessons for future thinking about the contribution of agriculture to: 1) poverty alleviation and rural livelihoods; 2)food security, human nutrition and health; 3) environmental sustainability and natural resource management. In discussing the way ahead, a number of major research challenges, as well as policy questions are outlined. These include the interrelations between climate change and food security and environmental degradation, increased demand for biofuels and animal feed, and competing claims on natural resources, and rural development and livelihood strategies in low-income countries.
Keywords: Life sciences; Geotechnical engineering; Agriculture; Ecology; Environment; Development economics; Life Sciences; Agriculture; Environment, general; Development Economics; Ecology; Geotechnical Engineering & Applied Earth Sciences; Electronic books